(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Photodegradation effect to natural plant waste under solar irradiation was investigated. Five plants waste namely, Averrhoe Bilimbi, Eugenia Clavifora, Elaies Guineensis, Terminalia cattapa and Clidemia hirta were selected from all over the states. Main purpose of this research was to study the stability of natural dye in presence of sunlight radiation for future solar cell applications. FTIR and UV-Vis absorption were used to investigate the optical properties of dye. Eugenia Clavifora was clearly revealed that it took more than 10 weeks to degrade and required 64% of degradation percentage. Optical energy gap was observed at 2.04 eV before exposure, while 2.15 eV after exposure of sunlight. Efficiency of Eugenia Clavifora hybrid solar cells was leading at the highest performance of 1.33%. This clearly shows that Eugenia Clavifora can be used as a natural photosensitizer thus enhancing the efficiency of any solar cell applications.